Synthesis and evaluation of the antifungal and antibiofilm potential of aminochalcones - Rocha Garcia, Mayara Aparecida [UNESP]; Sardi, Janaína de Cássia Orlandi; dos Santos, Mariana Bastos [UNESP]; Lazarini, Josy Golsoni; Rosalen, Pedro Luiz; Regasini, Luis Octávio [UNESP] (Springer Nature, 2025)
Candida is a commensal fungus of clinical interest that commonly lives in oral cavity and intestine but can become an opportunist microrganism and cause severe infections. A serie of 10 aminochalcones were designed and synthetized to obtain compounds anti-Candida with potent and broad-spectrum activity. The most active compound J34 demonstrated excellent in vitro activity against Candida albicans, Candida tropicalis, Candida parapsilosis, Candida glabrata and Candida krusei with minimum inhibitory concentration between 1.9 and 7.8 µg/mL. The association of aminochalcone J34 with amphotericin B demonstrated synergistic effect against C. albicans, with Fractional Inhibiroty Concentration Index (FICI) value of 0.5. Subinhibitory concentration of J34 inhibited the C. albicans adhesion to human keratinocytes. Treatment with J34 reduced C. albicans biofilm formation, as well as acts on preformed biofilm in concentration-dependent mode. Time-kill curve demonstrated that J34 had fungicidal action after 12 h of treatment. Preliminary mechanism of action study showed J34 interacts with membrane ergosterol but does not act on fungal cell wall of C. albicans. In additon, in vivo studies using Galleria mellonella indicated low toxic effect of chalcone J34 after 72 h of treatment.
Keywords: Antifungal; Chalcones; Ergosterol; Molecular docking